Antioxidant Activitvity and Immunomodulator of Indonesia Black Rice(Oryza sativa L. indica) Extract - Fadjar Kurnia Hartati (Journal of Global Pharma Technology, 2017)
The aim of this study to explore the foodstuffs potentially as an immunomodulator for use of synthetic immunomodulatory in the long term, in addition to considering also has negatively affect to the organs. The materials normally used as an immunomodulator is a substance containing phenol and flavonoid that has antioxidant activity. One of them is Indonesia black rice. This study was performed by in vitro test so that the samples that tested were in the extract form. Extracts were tested were ethanol and water extract of black rice. The use of water as a solvent extract because the sample is food, While ethanol is also used because ethanol is not toxic and the compounds present in black rice are also polar so polar that they can be used in dissolving polar and semi-polar compounds. Each extract was measured levels of phenol, antioxidant activity and its effects on lymphocyte proliferation (as an organ where immune cells produced). The treatment was health control, pain control, 50,100 and 200µg/ml. The results showed that ethanol extract of black rice and water containing phenol compound and has activity as an antioxidant, it also very potential as immunomodulators because the extract can increase lymphocyte proliferation.Keywords: immunomodulator, ethanol, water, Indonesia black rice.